(untitled) (Biological Sciences - PJSIR, 1999)
The oil was examined on a Pye-Unicam 104 gas chramatograph with FID detector and WCOT-SE-30 column. Various components were identified by their retension time and co-injection of standard samples (Singh and Sinha 1981). Percentage composition of individual components was calculated on the basis of peak area using SP-41 00 (Spectra- Physics) computing integrator.